ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PT BANK RAKYAT INDONESIA (PERSERO) TBK - Wisheila Inzaghia Ayunisa; Muhammad Imron; Andik Susanto (Universitas Merdeka Madiun, 2024)
This study aims to determine the financial performance of PT Bank Rakyat Indonesia (Persero) Tbk using the rations of liquidity, profitability, and solvency. This type of research is a type of quantitative descriptive analysis research with data collection techniques used are documentation and literature study. The data analysis techniques used is the analysis of liquidity, solvency, and profitability rations. The sample in this study is the balance sheet and profit/loss statement for the last 4 years published from the official website www.bri.co.id for the period 2019 to 2022. the result showed that the liquidity rations, namely the quick ratio, asset to loan ratio, and loan to deposit ratio (LDR) were in very good condition in accordance with BI standarts. In the profitability ratio, namely net profit margin, return on asset, and return on equity in a very good condition in accordance with BI satndarts. And in the solvency ratio, namely the primary ratio, capital ratio, and capital adequacy ratio (CAR) in very good condition in accordance with BI standarts.